DOMINASI WANITA HINDU DALAM PELAKSANAAN UPACARA KEAGAMAAN - Ariana, I Kadek Oka; Yasini, Ketut; Damayanti, Ni Luh Ayu Eka (Widya Genitri : Jurnal Ilmiah Pendidikan, Agama dan Kebudayaan Hindu, 2025)
Hindu women in West Tolai Village are more dominant in carrying out the Tawur Agung Kesanga ceremony than men. When carrying out religious ceremonies there should be cooperation between men and women so that activities can run smoothly. The aim of this research is to determine the causes and impacts of the dominance of Hindu women in religious ceremonies. The theories used are nurture theory and reception theory. This type of qualitative descriptive research, with data collection techniques: observation, interviews, literature and documentation. Determining informants used purposive sampling technique. From the research results it was concluded: 1) factors that Hindu women dominate the implementation of the Tawur Kesanga ceremony include: a. Traditional Role, b. Social norms and gender expectations, c. Involvement in traditional activities, d. Women as magic in the family, e. Women find it easier to communicate, f. Multitasking ability, g. Spiritual heritage and cultural knowledge, p. The role of women in ceremonial celebrations. 2) The implications of holding religious ceremonies dominated by Hindu women include: a. The role of religious celebrations is to provide a sense of peace, b. Inclusiveness and involvement of women in religious celebrations, c. Renewal of traditions, d. The important role of women in religion, e. Breaking down gender stereotypes.